Effects of thymoquinone and curcumin on the regeneration of rat livers subject to 70% hepatectomy - Gozeneli,Orhan (2018)
Abstract Purpose: To investigate thymoquinone, curcumin and a combination of these two drugs were effective or not at the growth of liver. Methods: Forty female Wistar-Albino rats distributed into five groups of eight rats each, control, thymoquinone, curcumin, and thymoquinone/curcumin groups. Pathological specimens were studied using the Ki-67 Proliferation Index(PI); and arginase(Arg), tissue plasminogen activator(tPA), ceruloplasmin(Cer) and nitric oxide(NO) were studied in biochemical analysis. Results: Our results showed that Ki-67 proliferation index was low in Groups 1. The proliferation coefficient was significantly higher in the Group 2 and Group 4 than in the Group 1 and Group 3.(P < 0.001 between Groups 1 and 2, 1 and 4, and 3 and 4). There was no difference between Groups 2 and 4 (P = 1). The results of the biochemical Arg, tPA and Cer test showed statistically between the Group 1 and Group 2. NO showed significant differences Group 1 and 3. Conclusions: Thymoquinone and curcumin both have known positive effects on the organism. Histological and biochemical tests showed that thymoquinone is more effective than curcumin.